Nucleic Acid Nanostructures for Chemical and Biological Sensing. Issue 20 (4th April 2016) - Chandrasekaran, Arun Richard; Wady, Heitham; Subramanian, Hari K. K.
Abstract : The nanoscale features of DNA have made it a useful molecule for bottom‐up construction of nanomaterials, for example, two‐ and three‐dimensional lattices, nanomachines, and nanodevices. One of the emerging applications of such DNA‐based nanostructures is in chemical and biological sensing, where they have proven to be cost‐effective, sensitive and have shown promise as point‐of‐care diagnostic tools. DNA is an ideal molecule for sensing not only because of its specificity but also because it is robust and can function under a broad range of biologically relevant temperatures and conditions. DNA nanostructure‐based sensors provide biocompatibility and highly specific detection based on the molecular recognition properties of DNA. They can be used for the detection of single nucleotide polymorphism and to sense pH both in solution and in cells. They have also been used to detect clinically relevant tumor biomarkers. In this review, recent advances in DNA‐based biosensors for pH, nucleic acids, tumor biomarkers and cancer cell detection are introduced. Some challenges that lie ahead for such biosensors to effectively compete with established technologies are also discussed. Abstract : DNA‐based biosensors are cost‐effective, sensitive and show promise as point‐of‐care diagnostic tools. DNA is an ideal molecule for sensing not only because of its specificity and controllability but also because of its robustness and ability to function under a wide range of biologically relevant temperatures and conditions. In this review, recent advances in DNA‐based biosensors for pH, nucleic acid and biomarker detection are introduced.